Biochemical Verification of Tobacco Use and Abstinence: 2019 Update. Issue 7 (1st October 2019) - Benowitz, Neal L; Bernert, John T; Foulds, Jonathan; Hecht, Stephen S; Jacob, Peyton; Jarvis, Martin J; Joseph, Anne; Oncken, Cheryl; Piper, Megan E
Abstract: Background: The changing prevalence and patterns of tobacco use, the advent of novel nicotine delivery devices, and the development of new biomarkers prompted an update of the 2002 Society for Research on Nicotine and Tobacco (SRNT) report on whether and how to apply biomarker verification for tobacco use and abstinence. Methods: The SRNT Treatment Research Network convened a group of investigators with expertise in tobacco biomarkers to update the recommendations of the 2002 SNRT Biochemical Verification Report. Results: Biochemical verification of tobacco use and abstinence increases scientific rigor and is recommended in clinical trials of smoking cessation, when feasible. Sources, appropriate biospecimens, cutpoints, time of detection windows and analytic methods for carbon monoxide, cotinine (including over the counter tests), total nicotine equivalents, minor tobacco alkaloids, and 4-(methylnitrosamino)-1-(3-pyridyl)-1-butanol are reviewed, as well as biochemical approaches to distinguishing cigarette smoking from use of electronic nicotine delivery devices (ENDS). Conclusions: Recommendations are provided for whether and how to use biochemical verification of tobacco use and abstinence. Guidelines are provided on which biomarkers to use, which biospecimens to use, optimal cutpoints, time windows to detection, and methodology for biochemical verifications. Use of combinations of biomarkers is recommended for assessment of ENDS use. Implications: Biochemical verification increases scientific rigor, but there are drawbacks that need to be assessed to determine whether the benefits of biochemical verification outweigh the costs, including the cost of the assays, the feasibility of sample collection, the ability to draw clear conclusions based on the duration of abstinence, and the variability of the assay within the study population. This paper provides updated recommendations from the 2002 SRNT report on whether and how to use biochemical markers in determining tobacco use and abstinence.